Suicídio no Brasil (2000-2022): tendências temporais e áreas de risco da mortalidade em estudo de base populacional - Souza, Danilo de Gois (2024)
Introduction: Suicide is among the main causes of death in the world, presenting itself as a serious public health problem. Its incidence has grown in several countries, affecting individuals of different age groups and generating significant social and economic costs. Brazil is among the ten countries in absolute numbers of suicide cases, a fact that leads to high costs for the health system, making this reality a serious public problem. The use of temporal, spatial and spatio-temporal analysis techniques can contribute to the characterization of mortality in the country, defining priority areas and populations for attention, which can direct the development and implementation of public policies to reduce suicide. Objective: To analyze the spatial, temporal and spatio-temporal distribution of suicide mortality in Brazil from 2000 to 2022. Materials and methods: Ecological, time series study, with spatial and spatio-temporal analysis, using secondary data from all deaths occurring in Brazil from 2000 to 2022 registered in the Mortality Information System. Temporal trends were calculated using the Poisson regression method using Joinpoint Regression. Spatial statistical inferences were made and choropleth maps were produced using TerraView and QGIS software. Spatiotemporal analysis was performed to identify spatiotemporal clusters of high risk for suicide mortality through SaTScan. Results: 240,843 deaths by suicide were recorded in Brazil throughout the study period. The Southeast region had the highest percentage of deaths by suicide (37.59%). The majority of deaths corresponded to male individuals (78.74%), white (51.18%), single (50.26%), aged between 20 and 59 years (75.35%) with education between 4 and 7 years of study (22.74%). The majority of deaths were caused by intentional self-harm by hanging, strangulation and suffocation (64.13%). The temporal analysis of suicide mortality in Brazil by regions, sex and age group revealed an increasing trend with an AAPC of 2.9 (95%CI: 2.6 to 3.0; p-value: <0.05). The distribution of crude and smoothed suicide death rates was displayed on the maps. During the study period, it was observed that the crude rates reveal areas of high mortality in the South, Central-West and North of the country. As for the smoothed rates, it was noted that they exhibit higher rates of suicide mortality in the southern and northern regions, with more discreet numbers in the Central-West region. Conclusion: A worrying increasing trend in suicide mortality in all regions of Brazil was particularly pronounced in the Northeast and North regions. It is noteworthy that the most significant increases in mortality were observed among men, adolescents, and young adults. Through spatial analyzes and spatio-temporal scans, we identified a heterogeneous distribution of suicide mortality, with the South and Central-West regions being the areas at greatest risk. Faced with these alarming trends, there is an imperative need to quickly promulgate comprehensive intersectoral public policies that cover the entire Brazilian territory, adapting strategies to regional needs.